2020
DOI: 10.1002/cb.1858
|View full text |Cite
|
Sign up to set email alerts
|

Managing the aftermath: Scapegoating as crisis communication strategy

Abstract: Should firms struggling with a brand crisis use scapegoating, the assignment of blame to another entity? Across three studies, we offer evidence of the value of scapegoating. We show that when firms use scapegoating, they reduce consumers' attributions of a firm's crisis responsibility, controllability, and stability. Compared to other strategies, including no response, denial, apology, and justification, scapegoating is most effective at reducing these attributions. However, attributions of crisis controllabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Various studies demonstrate that the effectiveness of crisis response strategies is primarily influenced by the crisis's nature and the characteristics of the involved organization [46,51]. These studies also reveal that the efficacy of crisis communication strategies is dynamic and subject to continual change.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies demonstrate that the effectiveness of crisis response strategies is primarily influenced by the crisis's nature and the characteristics of the involved organization [46,51]. These studies also reveal that the efficacy of crisis communication strategies is dynamic and subject to continual change.…”
Section: Discussionmentioning
confidence: 99%
“…Underdog and top‐dog brands have been well studied in the contexts of brand positioning (He et al, 2020; Li & Zhao, 2018; Schmidt & Steenkamp, 2022; Tang & Tsang, 2020) and communication appeals (Antonetti & Baghi, 2021; Moisio et al, 2021). Tang and Tsang (2020) suggested that many marketers opt to position their brands as underdogs—emphasizing the brand's journey and challenges en route to their current success—because customers can easily identify with the struggles of underdog brands.…”
Section: Theorymentioning
confidence: 99%
“…In other words, consumers try to determine why the product has failed and the reason they infer affects their attitudes and behavior toward the brand. When the crisis is determined to be intentional, consumers are more willing to complain and their evaluation of the brand deteriorates (Kim and Yim, 2021; Moisio et al , 2021), whereas when the crisis is deemed to be accidental, consumers are more inclined to be forgiving (Puzakova et al , 2013; Srinivasan and Sarial-Abi, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%